2023
DOI: 10.3390/ijms24087288
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Mediated Neuropathies: Pathophysiology and Management

Abstract: Dysfunction of the immune system can result in damage of the peripheral nervous system. The immunological mechanisms, which include macrophage infiltration, inflammation and proliferation of Schwann cells, result in variable degrees of demyelination and axonal degeneration. Aetiology is diverse and, in some cases, may be precipitated by infection. Various animal models have contributed and helped to elucidate the pathophysiological mechanisms in acute and chronic inflammatory polyradiculoneuropathies (Guillain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 311 publications
0
9
0
2
Order By: Relevance
“…GBS is an inflammatory polyneuropathy characterized by progressive flaccid ascending and symmetric muscle weakness associated with motor features and the presence or absence of sensory symptoms [ 2 ]. GBS is subclassified into classic forms, which present with acute flaccid paralysis of all four limbs, and localized forms, including pharyngeal–cervical–brachial weakness, acute pharyngeal weakness, paraparetic GBS, and bifacial weakness with paresthesias.…”
Section: Discussionmentioning
confidence: 99%
“…GBS is an inflammatory polyneuropathy characterized by progressive flaccid ascending and symmetric muscle weakness associated with motor features and the presence or absence of sensory symptoms [ 2 ]. GBS is subclassified into classic forms, which present with acute flaccid paralysis of all four limbs, and localized forms, including pharyngeal–cervical–brachial weakness, acute pharyngeal weakness, paraparetic GBS, and bifacial weakness with paresthesias.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that, in CIPN rats, there was a meaningful correlation between overlapping mRNAs and many immune cells. According to the immune infiltration analysis of hub genes, Cdh1 mainly correlates with plasmacytoid dendritic cells and macrophages, which can modulate the function of nociceptor sensory neurons and the development of neuropathies [ 59 , 60 ]. Fas and P2ry2 are negatively correlated with monocytes, Satb2 is positively correlated with Type 2 T helper cells, and Zfhx2 is closely related to T cells CD4 memory resting, suggesting their importance in CIPN and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Guillain-Barré syndrome (GBS) is an inflammatory polyneuropathy distinguished by a gradual onset of symmetrical, flaccid hypoxia in the ascending extremities, accompanied by motor symptoms with or without sensory manifestations. 1 It is a severe inflammatory peripheral radiculopathy and neuropathy with a reported global incidence of about 100,000 new cases per year. It is characterized by progressive limb weakness, sensory deficits, cranial nerve involvement, tendon areflexia, and cerebrospinal fluid (CSF) albuminocytological dissociation.…”
Section: Introductionmentioning
confidence: 99%